1974
DOI: 10.1021/ic50135a017
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical bis-phosphorus ligands. IV. Group VI metal carbonyl derivatives of diphenylphosphinomethyl and diphenylphosphinomethyl phosphinites, (C6H5)2P(CH2)nOP(C6H5)2, n = 1 or 2, and an unusual phosphorus chemical shift chelate effect

Abstract: The synthesis of the new ligand (C6H5)2PCH2OP(C6H5)2 is reported. Coordination compounds of this ligand and its analog (C6Hs)2PCH2CH2OP(C6H5)2 with chromium, molybdenum, and tungsten carbonyls and with PdCl2 are reported with 31P and • nmr data, including phosphorus-phosphorus and phosphorus-tungsten coupling constants where appropriate. Phosphorus nmr data are also reported for (C6Hs)2P(CH2)nP(C6H5)2M(CO)4, where M = Cr, Mo, or W and n-1,2, or 3. An unusually large downfield phosphorus coordination shift is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(35 citation statements)
references
References 3 publications
4
31
0
Order By: Relevance
“…Our results for Sn(I1) and Pb(I1) complexes of etp, PP,(PH)+, and PPP(PH)+ (see Table 2 "3J(PB-PB,)") is greatly reduced in magnitude on coordination, suggesting that the trends outlined hold for these two Main Group elements also. Further, as described above, our analysis of the spectra of the two M(PPP(PH))3+ complexes shows the existence of a sizeable through-metal coupling from PA to Pas, in concert with the suggestion of Grim et al (6,7). It is disconcerting, therefore, to find that the coupling between adjacent phosphorus atoms of polyphosphine oxides is reduced markedly on chelate ring formation also (Table 3 and ref. 18).…”
Section: Phosphorus-phosphorus Coupling In Complexessupporting
confidence: 80%
See 2 more Smart Citations
“…Our results for Sn(I1) and Pb(I1) complexes of etp, PP,(PH)+, and PPP(PH)+ (see Table 2 "3J(PB-PB,)") is greatly reduced in magnitude on coordination, suggesting that the trends outlined hold for these two Main Group elements also. Further, as described above, our analysis of the spectra of the two M(PPP(PH))3+ complexes shows the existence of a sizeable through-metal coupling from PA to Pas, in concert with the suggestion of Grim et al (6,7). It is disconcerting, therefore, to find that the coupling between adjacent phosphorus atoms of polyphosphine oxides is reduced markedly on chelate ring formation also (Table 3 and ref. 18).…”
Section: Phosphorus-phosphorus Coupling In Complexessupporting
confidence: 80%
“…refs. 6-9, and a change of sign may occur also (6,7). For the formation of a five-membered chelate ring with a hydrocarbon backbone, a reduction in magnitude is found (e.g.…”
Section: Phosphorus-phosphorus Coupling In Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a downfield shift is generally also observed for five-membered chelates in [M(L 2 )(CO) 4 ] complexes (M W, Mo, Cr). [18] A single crystal X-ray structure determination ( Figure 2) provided conclusive structural characterization of this new ligand system. The octahedral Mo-coordination of 18 is (20).…”
Section: Resultsmentioning
confidence: 90%
“…An alternative condensation strategy, involving a transition metal-assisted route, has been used to access new precomplexed P-C-O-P bidentate ligands. Whereas examples are known in the literature, albeit rare, for the nonmetal based coupling of two phosphorus species with P-C-O-P formation [9][10][11], the use of a metal template reaction to directly access the preformed complex is particularly attractive [12]. Previous studies have shown that unusual P-C bond cleavage reactions at Rh [13], Pd [14] or Pt [14] centres can proceed readily in complexes of P(CH 2 OH) 3 affording unusual bidentate ligands with a P-C-O-P framework.…”
mentioning
confidence: 99%